Do dissolved heavy metals enter the food webs of alpine streams? - Tolotti, M.; Maule, A.; Brighenti, S.; Voto, G.; Bruno, M. C. (country:IT, 2024)
The Euregio project “ROCK-ME”: Geochemical response of Alpine Rock Glaciers to global warming” investigates the origin, export, and ecological effects of trace elements in Alpine river networks influenced by permafrost (i.e., rock glacier) thawing and glacier retreat. Permafrost degradation and glacier recession can cause elevate export of solutes, including heavy metals, into Alpine headwaters while the contribution from groundwater is usually negligible. However, the ecological effects remain understudied. We assessed if and how the enrichment in trace element observed in high altitude Alpine streams causes biomagnification processes in the aquatic organisms by characterizing the food webs of different stream types (i.e., fed by intact and relict rock glaciers, and reference spring draining an area without periglacial landforms/glaciers/permafrost) using δ13C and δ15N isotopic ratios analysis, and measuring the content of trace elements in each component of the food web. The investigation was conducted in late summer 2022 in two catchments in South-Tyrol: Lazaun in Schnalstal/Val Senales and Madritsch/Madriccio in Martell/Martello Valleys. The analysed matrices were: coarse and fine particulate organic matter (CPOM and FPOM), epilithic biofilms, bryophytes, and benthic invertebrates of different taxa characterized and grouped by feeding habit (omnivore, carnivore, herbivore, detritivore). The same trace elements were measured in the water of each stream type. As expected, most of the biomagnification occurred in streams originating from intact rock glaciers. However, due to the paucity of predators in the benthic community and hence in the food web, biomagnification was more pronounced (up to 11 times the content in the basal sources) for the first levels of the food web. Comparable or higher levels of bioaccumulation in the second food web level occurred only in two of the studied streams